Transformasi Pendidikan di Indonesia: Menuju Sistem yang Inklusif dan Berkualitas - Sari, Lulita Kayla (Maliki Interdisciplinary Journal, 2025)
The transformation of education in Indonesia is an ongoing effort to create an inclusive and quality education system, with the main goal of providing equal access for all children, regardless of social and economic background. This article discusses various policies and steps that have been taken by the government, including the implementation of the 2013 Curriculum and the Smart Indonesia Program, which aims to improve participation and quality of education. In addition, this article identifies challenges that are still being faced, such as the disparity in access between urban and rural areas, as well as the importance of improving the quality of teaching through teacher training and the use of technology. It was also emphasized that character education and life skills must be an integral part of the curriculum to prepare a generation that is not only academically intelligent, but also has good integrity and social skills. By involving community participation and collaboration between various stakeholders, it is hoped that the transformation of education in Indonesia can produce a better and sustainable system, and be able to answer global challenges in the future.